(untitled) (Hungarian Journal of Industry and Chemistry, 2011)
A simple dynamic model of a synchronous motor is developed in this paper based on first engineering principles that describe the mechanical phenomena together with the electrical model. The constructed state space model consists of nonlinear state equations and bi-linear output equations. The developed model has been verified under the usual regulated operating conditions when the speed and the torque are controlled, the manipulated input is the network voltage and the exciter voltage. The effect of load on the controlled synchronous motor has been analyzed by simulation using PI controllers. Model parameter sensitivity analysis has been applied to determine the model parameters to be estimated.